Aumento de la producción de la línea dos del área de envasado de Cervecería Nacional utilizando trabajo estandarizado - Alvear Sarmiento, Alejandra Nicole (2016)
This degree work is a proposal for improving the productivity of the Line Two of the Bottling Area in “Cervecería Nacional” plant in Cumbayá-Ecuador using the standardization process in the bottleneck. To determine the proposal, we collect the data of Line Two (beer production) and from the bottleneck of the line, in order to define the process on which we would focus. We study the process time, that has the mayor variability in the bottleneck and the opportunities for improvement. Which were differences in timing and processes sequences. The solution proposed was process standardization of the Starting and Finishing phases. Where a correct sequence has been set to a defined time, and the activities that do not add value to the process were eliminated. Finally, the results were estimated, considering the activities defined in the improvements proposed. The results were reduction of the process variability, the efficiency improvement of the bottleneck and a net income by $ 80,000 per year.